Cerium Oxide Decorated Graphene Nanolayers Filled Polyvinylidene Fluoride Nanofibers as Optical Piezoelectric Sensors - Nour Bader (22391686) (2025)
This article introduces the fabrication of optical piezoelectric sensors using cerium oxide (CeO)‐decorated graphene nanolayers incorporated into polyvinylidene fluoride hexafluoropropylene (PVDF‐HFP) fibers. Electrospinning method is employed to create the composite nanofibers, resulting in a highly aligned and consistent fibrous structure. Graphene nanolayers are functionalized onto CeO nanoparticles using a rapid and scalable solution‐based process. The resulting hybrid composite material exhibited superior piezoelectric characteristics compared to pure PVDF‐HFP. A fiber Bragg grating sensor is integrated into the PVDF‐HFP nanofiber composite to enable optical sensing. As a strain gauge, the sensor detected variations in fiber length caused by mechanical deformation. The addition of CeO‐decorated graphene nanolayers enhanced the piezoelectric response of the PVDF‐HFP nanofibers, producing an electrical signal proportional to the applied mechanical stress. The sensor's performance is evaluated under various mechanical stimuli, including compression, bending, and vibration. The sensor demonstrated excellent sensitivity, repeatability, and fast response times. The proposed optical piezoelectric sensor, based on PVDF‐HFP nanofibers filled with CeO‐decorated graphene nanolayers, shows great potential for applications in robotics, wearable electronics, and structural health monitoring. This sensor technology is highly appealing for next‐generation smart materials and devices due to its enhanced piezoelectric properties, optical sensing capabilities, and mechanical resilience. Other Information Published in: Macromolecular Materials and Engineering License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/mame.202400350